Epidemiological Situation of Monkeypox Transmission by Possible Sexual Contact: A Systematic Review - León-Figueroa, Darwin A. (2022)
Monkeypox (MPX), a zoonotic infection caused by the monkeypox virus (MPXV), has re-emerged worldwide with numerous confirmed cases with person-to-person transmission through close contacts, including in sexual networks. Therefore, this study aimed to determine the epidemiological situation of monkeypox transmission by possible sexual contact. A systematic literature review was conducted using PubMed, Scopus, Web of Science, and Embase databases until 18 August 2022. The key search terms used were “monkeypox”, “sexual contact”, “sexual intercourse” and “sexual transmission”. A total of 1291 articles were retrieved using the search strategy. After eliminating duplicates (n = 738) and examining by title, abstract, and full text, 28 studies reporting case reports of monkeypox with a detailed description of clinical features, sexually transmitted diseases, method of diagnosis, location and course of skin lesions, and treatment were included. A total of 4222 confirmed cases of monkeypox have been reported, of which 3876 monkeypox cases are the result of transmission by sexual contact distributed in twelve countries: 4152 cases were male with a mean age of 36 years. All confirmed cases of monkeypox were diagnosed by reverse transcriptase-polymerase chain reaction (RT-PCR). The most frequent clinical manifestations were fever, lymphadenopathy, headache, malaise, and painful perianal and genital lesions. The most frequent locations of the lesions were perianal, genital, oral, trunk, upper and lower extremities. Patients were in good clinical condition, with treatment based on analgesics and antipyretics to relieve some symptoms of monkeypox. A high proportion of STIs and frequent anogenital symptoms were found, suggesting transmissibility through local inoculation during close skin-to-skin or mucosal contact during sexual activity. The highest risk of monkeypox transmission occurs in men who have sex with men, and MPXV DNA could be recovered in seminal fluid. It is essential to establish health policies for the early detection and management of patients with monkeypox.